Solomon Islands : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
This 2004 Article IV Consultation highlights that the government of the Solomon Islands has moved rapidly to stabilize budgetary finances since the arrival in mid-2003 of the multinational Regional Assistance Mission to the Solomon Islands (RAMSI) that has restored law and order throughout the country. The budget finished the year with a deficit of just 1 1\2 percent of GDP, compared with 10 percent in 2002. Real GDP grew by an estimated 5 percent in 2003, helped by strong fish, copra, and cocoa production.